Minimally Invasive Neurosurgery for Spontaneous Intracerebral Hemorrhage—10 Years of Working Progress at National Taiwan University Hospital - Hsu, Chiu-Hao; Chou, Sheng-Chieh; Kuo, Lu-Ting; Huang, Sheng-Jean; Yang, Shih-Hung; Lai, Dar-Ming; Huang, Abel Po-Hao (Frontiers in neurology, 2022)
Intracerebral hemorrhage (ICH) is a life-threatening disease with a global health burden. Traditional craniotomy has neither improved functional outcomes nor reduced mortality. Minimally invasive neurosurgery (MIN) holds promise for reducing mortality and improving functional outcomes. To evaluate the feasibility of MIN for ICH, a retrospective analysis of patients with ICH undergoing endoscopic-assisted evacuation was performed. From 2012 to 2018, a total of 391 patients who underwent ICH evacuation and 76 patients who received early (<8 h) MIN were included. The rebleeding, mortality, and morbidity rates were 3.9, 7.9, and 3.9%, respectively, 1 month after surgery. At 6 months, the median [interquartile range (IQR)] Glasgow Coma Scale score was 12 (4.75) [preoperative: 10 (4)], the median (IQR) Extended Glasgow Outcome Scale score was 3 (1), and the median (IQR) Modified Rankin Scale score was 4 (1). The results suggested that early (<8 h) endoscope-assisted ICH evacuation is safe and effective for selected patients with ICH. The rebleeding, morbidity, and mortality rates of MIN in this study are lower than those of traditional craniotomy reported in previous studies. However, the management of intraoperative bleeding and hard clots is critical for performing endoscopic evacuation. With this retrospective analysis of MIN cases, we hope to promote the specialization of ICH surgery in the field of MIN.